Survival Analysis of Patients with High-Grade Gliomas Based on Data Mining of Imaging Variables - Zacharaki, E.I.; Morita, N.; Bhatt, P.; O'Rourke, D.M.; Melhem, E.R.; Davatzikos, C. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: The prediction of prognosis in HGGs is poor in the majority of patients. Our aim was to test whether multivariate prediction models constructed by machine-learning methods provide a more accurate predictor of prognosis in HGGs than histopathologic classification. The prediction of survival was based on DTI and rCBV measurements as an adjunct to conventional imaging. MATERIALS AND METHODS: The relationship of survival to 55 variables, including clinical parameters (age, sex), categoric or continuous tumor descriptors (eg, tumor location, extent of resection, multifocality, edema), and imaging characteristics in ROIs, was analyzed in a multivariate fashion by using data-mining techniques. A variable selection method was applied to identify the overall most important variables. The analysis was performed on 74 HGGs (18 anaplastic gliomas WHO grades III/IV and 56 GBMs or gliosarcomas WHO grades IV/IV). RESULTS: Five variables were identified as the most significant, including the extent of resection, mass effect, volume of enhancing tumor, maximum B0 intensity, and mean trace intensity in the nonenhancing/edematous region. These variables were used to construct a prediction model based on a J48 classification tree. The average classification accuracy, assessed by cross-validation, was 85.1%. Kaplan-Meier survival curves showed that the constructed prediction model classified malignant gliomas in a manner that better correlates with clinical outcome than standard histopathology. CONCLUSIONS: Prediction models based on data-mining algorithms can provide a more accurate predictor of prognosis in malignant gliomas than histopathologic classification alone. AUCarea under the curveB0baseline (T2-weighted) imageETenhancing tissueFAfractional anisotropyGBMglioblastoma multiformeHGGhigh-grade gliomaLGGlow-grade gliomaNETnonenhancing tissuerCBVrelative cerebral blood volumeROCreceiver operating characteristic analysisWHOWorld Health Organization